Clinical significance of microRNA-126 in Coronary artery disease patients. (14th October 2021) - Ali Sheikh, M S
Abstract: Background: Coronary artery disease (CAD) is major public health problem and the leading cause of premature death all over the world. Early diagnosis with adequate management of CAD patients can significantly reduce morbidity and mortality rate. Purpose: The purpose of this study was to explore the clinical significance of plasma miR-126 as a biomarker of stable angina pectoris patients and investigated the protective effects of hypoxic exposed HUVEC cell injury. Methods: Angiographically confirmed 127 stable coronary artery (CAD) patients, 55 healthy subjects and 18hours hypoxic (1% O2) HUVEC cells were included in this study. Results: The expression of miR-126 levels were remarkably down-regulated in stable CAD patients and hypoxic exposed HUVEC cells as compared with controls (p<0.001). Circulating plasma miR-126 was able to accurately differentiated stable CAD patients from healthy subjects with high sensitivity and specificity (AUC 0.928). The caspase-3 activity, apoptosis rate, LDH levels and intracellular ROS generation were significantly increased in 24hours hypoxic exposed HUVEC cells than normal control cells (p<0.001). On the contrary, over expressions of miR-126 were evidently reduced caspase-3 activity, apoptosis rate, LDH levels, intracellular ROS production and significantly improved HUVEC cellular viability (p<0.001). Moreover, TNF receptor-associated factor 6 (TRAF6) expressions were markedly increased in Hypoxic induced HUVEC cells, whereas mimic expression of miR-126 significantly decreased TRAF6 expression. Conclusion: Down-regulated miR-126 may consider as a potential risk factor for stable CAD patients and it may used as a possible biomarker for early evaluation of CAD patients. Mimic expression of miR-126 remarkably decreased caspase-3 activity, LDH secretions, ROS levels and markedly improved HUVEC cellular viability by down-regulating TRAF6 expression, suggesting a newer therapeutic target for CAD patients. FUNDunding Acknowledgement: Type of funding sources: None.